Recent acoustic energy harvesting methods and mechanisms: A review. (December 2021) - Patil, Avadhut T; Mandale, Maruti B
This review article summarises the mechanism of the acoustic energy harvester or converter which includes the compact structure of the piezoelectric element, electromagnetic transducer and Helmholtz resonator; different shapes of Helmholtz resonators, piezoelectric cantilever, acoustic metamaterial-based approach, electrostatic transduction method, auxetic structure of material and other techniques. The recently established methods of acoustic energy harvesting and converting mechanisms; devices are carefully reviewed, and their results are compared and listed in the table. The technique of energy conversion by using acoustic metamaterial will tend to be more efficacious due to its complexity and the structure. Even in the few noise attenuation applications, more metamaterial is used, where, with the help of the conversion mechanism, the noise or sound energy can be converted into electrical energy for small electronic applications. It is demonstrated that the acoustic energy-conversion technique will become an essential part of the environmental energy harvesting research field.